Trace metal distribution for water samples of Atair cruise AT275 - Anna Ebeling; Ole Klein; Nathalie Voigt; Daniel Pröfrock (PANGAEA, 2023)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in and around offshore wind farms of the German Bight between 06.03.2019 and 24.03.2019 within the context of the Hereon-BSH project OffChEm. The water samples were taken in metal-free GO-FLO sampling bottles, filtered over <0.45 μm polycarbonate filters into pre-cleaned LDPE bottles and acidified with nitric acid. The filtrates were then measured for their (trace) metal concentrations with ICP-MS/MS coupled online to a seaFAST preconcentration and matrix removal system.